Interactive effect of sowing and water stress on rate of LAI and yield of wheat (Triticum aestivum) - DHAKAR, RAJKUMAR; SEHGAL, VINAY KUMAR; CHAKRABORTY, DEBASISH; MUKHERJEE, JOYDEEP (The Indian Journal of Agricultural Sciences, 2021)
Understanding the behavior of crops under interactive effect of different abiotic stresses is the need of hour. Present study aimed to examine the interactive effect of late planting and deficit irrigation on wheat (Triticum aestivum L.) growth and development in semi-arid environment. The field experimentation with two planting dates and three levels of irrigation was conducted during rabi 2015-16 and 2016-17. The results showed that response of water stress on wheat growth and development behaved in similar manner as of that in late planting. The reduction in LAI, biomass, yield and yield attributes was observed under independent effect of water stress as well as late planting with varied magnitude. Noticeably, late sowing had large influence on rate of LAI change in the order of 20% and 47% in greening and senescence phase, respectively than deficit irrigation. The slowdown of LAI change in greening phase is also associated with faster senescence in late phase of crop growth. However, the additive effect was observed under combined water deficit and late planting conditions. It may be concluded that the co-existence of limited water availability and late planting is most detrimental to wheat growth and development ultimately on crop yields in semiarid environment. Therefore, suitable agronomic and breeding strategies must be devised to mitigate the hampering effect of combined reduced water availability and late planting conditions.